SYNOPTYCZNE UWARUNKOWANIA BURZ W PAŹDZIERNIKU 2020 ROKU W POLSCE - WARDOWSKI, DANIEL (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2020)
The aim of this study is to characterize the occurrence of severe thunderstorms and determine their synoptic conditioning in October 2020 in Poland. In the study, into account were taken three days, i.e. 4, 5 and 10 October, which showed the most intense storm activity. The study considers the number and area of lightning discharges over Poland, the synoptic conditions prevailing in Europe, as well as basic thermodynamic and kinematic indices. The storms in October 2020 were exceptional in comparison to the previous years. They were associated with the migration of cool atmospheric fronts across Poland and the exchange of old polar-marine air masses with polar-marine air masses, which generated the specific thermodynamics and, specifically, the kinetic conditions for the development of thunderstorm cells.